Stakeholder engagement in Johannesburg’s corridors of freedom urban regeneration vision - Quartey, Kofi Gyan (My University, 2020)
World Bank projections have indicated that by 2030, sixty percent of the global population will relocate to urban cities and will reach seventy percent in 2050. Moreover, over fifty percent of the global populace is experiencing unprecedented mobility challenges as a result of inefficient transportation infrastructure and services, primarily in developing countries. In line with Sustainable Development Goal 11, The National Development Plan, The Growth Development Strategy and the Integrated Development Plan, the City of Johannesburg Municipality are in the process of undertaking the Johannesburg TOD, previously called the Corridors of Freedom. The vision exists to address existing unequal mobility and spatial patterns characteristic of apartheid. In recognising the importance of Stakeholder engagement and its pivotal significance in mega-projects, this study investigated the stakeholder engagement aspect of some of the projects that fall within the ambit of the Corridors of Freedom vision. The investigation was undertaken through the lens of Freeman's stakeholder theory and contemporary urban planning theories, which advance that organisations or convenors of projects are obligated to act in the interest of their internal and external stakeholders. This research is based on pragmatist philosophy. Furthermore, methodological triangulation was achieved through extensive literature analysis, 23 semi-structured interviews (qualitative method), and 40 questionnaires (quantitative method). The literature review identified the research gap, which revealed that there was a need for literature to interrogate the process of policy formulation and participation implementation in community-level stakeholder engagements. The qualitative semi-structured interviews gathered information of the 3Cs, namely City Entity Professionals (CEPs),Contractors (Cs), and Community Representatives (CRs). Questionnaire aided in collecting information from the 4th C, Community Members (CMs). IBM SPSS was used to analyse the responses from CMs, from which descriptive statistics of frequencies and percentages were used to summarise the data. Cronbach’s alpha was used to test the internal reliability of the questionnaire, while Fischer’s exact test was used to determine the socio-demographic variables and public engagement measures. Content analysis was performed using NVivo 12 from the information obtained from the 3Cs. The study’s findings revealed the need for enforcement of by-laws, more extensive marketing and advertising of the CoF through partnerships with the creative industry, and across all social media platforms, early inclusion of communities in engagement practices, incentivising of participation, regular updates on project progress, the use of Stakeholder engagement software in managing stakeholder meeting outputs and consideration of disabled persons such as visually impaired in communication and informing CMs
A thesis submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, in fulfilment of the requirements for the degree of Doctor of Philosophy, 2020